Fulminant eosinophilic endomyocarditis in an asthmatic patient treated with pranlukast after corticosteroid withdrawal. Issue 3 (1st September 2001) - Hayashi, S; Furuya, S; Imamura, H
Abstract : Several cases of eosinophilic conditions including Churg-Strauss syndrome have been reported in association with the use of cysteinyl leukotriene receptor antagonists, including zafirlukast, montelukast, and pranlukast, in asthmatic patients. The case of a 26 year old woman with a three year history of asthma, rhinitis, and nasal polyps is reported in whom eosinophilia, pulmonary infiltrates, and fulminant eosinophilic endomyocarditis accompanied by cardiogenic shock developed during pranlukast treatment after corticosteroid withdrawal. Acute necrotising eosinophilic endomyocarditis was confirmed by endomyocardial biopsy. The patient recovered after intensive treatment, including mechanical assistance involving intra-aortic balloon pumping and steroid pulse therapy, along with the discontinuation of pranlukast. It is recommended that careful attention must be paid to signs of a systemic eosinophilic condition or even fulminant eosinophilic myocarditis in asthmatic patients who have begun treatment with antileukotriene drugs following withdrawal of steroids.